Characterization of lacrimal proline‐rich protein 4 (PRR4) in human tear proteome. Issue 13 (18th June 2014) - Perumal, Natarajan; Funke, Sebastian; Pfeiffer, Norbert; Grus, Franz H.
<x xml:space="preserve">Abstract</x> This study was initiated considering the lack of comprehensive characteristics profile of PRR4 in tears of healthy subjects. Therefore, detailed characterizations of PRR4 from basal tears employing in‐gel and in‐solution digestions for MS systems are presented herein. First, pooled tear samples (n = 10) were utilized to identify PRR4‐rich region/spots in 1DE/2DE gels employing LC‐MALDI‐MS and 1DE‐LC‐ESI‐LTQ‐Orbitrap‐MS systems. PRR4‐rich region and ten spots with vast polymorphisms (Mr: 17–30 kDa, pI: 3.0–6.6) were identified in 1DE and 2DE gels, respectively. In addition, combinations of four types of PTMs, which are methylation, acetylation, oxidation, and pyroglutamate formation, were identified in these ten PRR4 spots. Furthermore, a targeted data‐acquisition approach was utilized to identify PRR4 isoforms in individual tear samples (n = 61) by in‐solution digestion combined with a LC‐ESI‐LTQ‐Orbitrap‐MS system. Importantly, a new PRR4 isoform designated as PRR4‐N3 in addition to PRR4 (gi154448886) and pHL E1F1 (gi1050983) was identified. Moreover, different combinations of these three PRR4 isoforms identified in the individual tear samples could be categorized into six distinguished groups. Conclusively, these findings provide fundamental insight into the complex characteristics profile of PRR4 isoforms and their PTMs in tears of healthy individuals.